2019
DOI: 10.1002/hyp.13588
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the interaction of surface roughness and slope gradient in controlling rates of soil loss from sloping farmland on the Loess Plateau of China

Abstract: Surface roughness and slope gradient are two important factors influencing soil erosion. The objective of this study was to investigate the interaction of surface roughness and slope gradient in controlling soil loss from sloping farmland due to water erosion on the Loess Plateau, China. Following the surface features of sloping farmland in the plateau region, we manually prepared rough surfaces using four tillage practices (contour drilling, artificial digging, manual hoeing, and contour plowing), with a smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Rough surfaces were manually prepared with the four tillage practices of CP, MH, AD, and CD [29]; a control plot with a smooth surface was also prepared (CK: Figure 2). The practices were as follows: (1) CP represents a customary tillage technique for preparation of new soil for planting.…”
Section: Tillage Treatmentsmentioning
confidence: 99%
“…Rough surfaces were manually prepared with the four tillage practices of CP, MH, AD, and CD [29]; a control plot with a smooth surface was also prepared (CK: Figure 2). The practices were as follows: (1) CP represents a customary tillage technique for preparation of new soil for planting.…”
Section: Tillage Treatmentsmentioning
confidence: 99%
“…However, summer tillage tends to destroy the topsoil, creating bare soil on sloping land, and rainfall on the Loess Plateau is mostly concentrated during this period. When this bare sloping farmland is struck by raindrops during the rainy season, the soil structure is highly susceptible to damage and forms a soil crust, resulting in a reduced soil infiltration capacity and a surge in runoff; these conditions greatly increase the potential occurrence of soil erosion (Li et al, 2020;Wang et al, 2017). Studies have shown that approximately 60% of watershed runoff and sediment are sourced from sloping farmland due to natural and anthropogenic influences (Keesstra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The factors influencing soil erosion on loess slopes can be summarized into four categories: rainfall, soil erodibility, topography, and slope surface cover (Liu et al, 2019). By reducing the slope (Zhao et al, 2015;Li et al, 2019) and setting buffer steps (Duan et al, 2021a;Wen et al, 2021), we can effectively reduce the kinetic energy of runoff and control rill erosion (Wei et al, 2007;Fu et al, 2009;Zhao et al, 2013;Tang et al, 2020). For slope surface cover, erosion control can be achieved by, for example, planting trees and grass (Chen et al, 2018;Yan et al, 2021) or laying artificial turf (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%